Cloud-Based Accounting Systems: Apakah Meningkatkan Transparansi atau Risiko Kebocoran Data? - Suci Aulia; Rina Tjandra Kirana DP (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
The adoption of Cloud-Based Accounting Systems has increasingly expanded as part of digital transformation efforts aimed at enhancing transparency and the quality of financial reporting, while simultaneously raising concerns regarding data security risks. This study seeks to synthesize empirical evidence on the role of cloud-based systems as mechanisms for improving transparency or as potential sources of data breaches. A Systematic Literature Review was conducted following the PRISMA 2020 guidelines through searches in Scopus, CrossRef, SINTA, Garuda, and Google Scholar for the 2021–2026 period. Of the 482 articles initially identified, 34 studies met the inclusion criteria and were analyzed thematically. The findings indicate that most studies report improvements in accuracy, real-time access, and financial reporting quality. However, several studies also highlight cybersecurity threats, vendor lock-in risks, and regulatory compliance challenges. These results suggest the existence of a transparency–risk paradox that depends on technological readiness and organizational governance. Overall, the transparency benefits appear to be more dominant, but their effectiveness requires strengthened security controls and adequate digital governance.